Discipline in Stages: Regulating CD8+ Resident Memory T Cells - Mora-Buch, Rut; Bromley, Shannon K. (Frontiers in Immunology, 2021)
Resident memory CD8+ T (TRM) cells are a lymphocyte lineage distinct from circulating memory CD8+ T cells. TRM lodge within peripheral tissues where they provide rapid, local protection from pathogens and control tumor growth. However, dysregulation of CD8+ TRM formation and/or activation may contribute to the pathogenesis of autoimmune diseases. Intrinsic mechanisms, including transcriptional networks and inhibitory checkpoint receptors control TRM differentiation and response. Additionally, extrinsic stimuli such as cytokines, cognate antigen, fatty acids and damage signals regulate TRM formation, maintenance and expansion. In this review, we will summarize knowledge of CD8+ TRM generation and highlight mechanisms that regulate the persistence and responses of heterogeneous TRM populations in different tissues and distinct microenvironments.